Analysis of Economic Pressure, Coping Strategies, Social Support and Family Resilience in Sandwich Families in Bogor City (Journal of Family Sciences, 2025)
The sandwich family structure refers to individuals who are responsible for supporting both elderly parents and children simultaneously. This dual responsibility can create significant pressure and impact family resilience. This study aims to analyse family characteristics, economic pressures, coping strategies, social support, and the relationships between these variables and their influence on family resilience. This study uses a cross-sectional study design with a sample of 120 wives from complete families who live with elderly parents. Data collection was carried out in March-May 2023 in Bogor City using a questionnaire and processed using SPSS and SEM PLS. The results showed that the husband and wife were in the early adult group with an average junior high school education level and more than half of the per capita income were categorized as poor. The average economic pressure, coping strategies and social support are in the low category, while family resilience is in the moderate category. Husband and wife education and per capita income have a significant positive relationship with family resilience. Economic pressure has a significant negative direct effect on family resilience, while coping strategies and social support have a significant positive direct effect on family resilience. This research shows the importance of increasing per capita income, coping strategies and social support in increasing the resilience of sandwich families in Bogor city.